2016
DOI: 10.18632/oncotarget.12768
|View full text |Cite
|
Sign up to set email alerts
|

A role for the vitamin D pathway in non-intestinal lesions in genetic and carcinogen models of colorectal cancer and in familial adenomatous polyposis

Abstract: Vitamin D is implicated in the etiology of cancers of the gastrointestinal tract, usually characterized by alteration in the APC/β-catenin/TCF tumor suppressor pathway. The vitamin D receptor (VDR) is also implicated in cardiovascular and skin diseases as well as in immunity. Activated VDR can indirectly alter β-catenin nuclear localization and directly suppress β-catenin/TCF mediated transcriptional activity. We treated VDR null mice with the carcinogen azoxymethane (AOM) and generated mice bearing a mutated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Vitamin D is not only a vitamin, but also a multifunctional pro-hormone and a precursor to calcitriol [1,25-dihydroxy-vitamin D3 (1,25(OH) 2 D 3 )], which is a potent steroid hormone [ 18 ]. The etiology of vitamin D deficiency-mediated cancers is characterized by an alteration in the oncogenic Wnt/β-catenin signaling pathway or the APC/β-catenin/TCF tumor suppressor pathway [ 5 , 19 , 20 ]. So et al [ 21 ] found that administration of 1,25(OH) 2 D 3 or its analogs decreased Notch ligand levels, inhibited Notch 1 signaling, and reduced the CSC numbers among breast cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin D is not only a vitamin, but also a multifunctional pro-hormone and a precursor to calcitriol [1,25-dihydroxy-vitamin D3 (1,25(OH) 2 D 3 )], which is a potent steroid hormone [ 18 ]. The etiology of vitamin D deficiency-mediated cancers is characterized by an alteration in the oncogenic Wnt/β-catenin signaling pathway or the APC/β-catenin/TCF tumor suppressor pathway [ 5 , 19 , 20 ]. So et al [ 21 ] found that administration of 1,25(OH) 2 D 3 or its analogs decreased Notch ligand levels, inhibited Notch 1 signaling, and reduced the CSC numbers among breast cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…Although colon tumors develop in Apc 1638N/+ mice, their incidence and number is low and their formation takes 10–12 months (2, 6, 8). Treating Apc 1638N/+ mice with “Western style” diet (9) or crossing them with other genetically engineered mutant or knockout mice (6, 1017) promotes multiplicity and sometimes progression of tumors in SI and/or colon. Similarly, conditional knockout of Apc in colonic epithelial cells leads to selective colon tumor formation (18, 19).…”
Section: Introductionmentioning
confidence: 99%